Voting After Violence: How Combat Experiences and Postwar Trauma Affect Veteran and Voter Party Choices in Croatia's 2003 Postwar Elections. Issue 2 (April 2020) - Lesschaeve, Christophe
This article investigates the role of war experiences on voters and veterans' party choices in postwar elections. The literature has looked at the relation between military experience and electoral behavior, and at the political consequences of war-related psychological distress, yet has never integrated the two. This article looks at the war experiences and specifically the development of war trauma on the likelihood of casting a vote for a nationalist party during a postwar election. Based on a 2003 survey of 1, 000 Croatian voters, I find that veterans of Croatia's war of independence are more likely to vote for nationalist parties. However, voters who showed signs of trauma were less likely to vote for these parties. In addition, veterans suffering from psychological trauma after the war were far less likely to vote for nationalist parties.